Hopelessness and suicide ideation in ostomy patients: a mixed method study - Sarabi,Nasrin (2020)
Abstract Introduction: It is important to characterize patients’ mental health problems since the association between mental adjustment and life expectancy has stabilized in these patients. So, the present study was conducted to determine the prevalence of suicidal ideation and hopelessness in patients with ostomy. Method: A mixed method strategy (cross-sectional and content qualitative analysis) was done in Educational Hospitals in Tehran in 2019. Beck Suicide Ideation (19 item) and Beck Hopelessness (20 item) self-assessment questionnaires and unstructured interview were used for data collection. Data were expressed as frequency and percentage and independent t-test. Analysis was done in the Statistical Package for the Social Sciences (SPSS) 16.0 and conventional content analysis. Results: Three months after surgery, 3% had low suicidal ideation and 97% had high risk suicidal ideation. This rate 6 months after surgery was 16% with low suicidal thoughts and 84% with high risk suicidal thoughts. In the case of hopelessness 3 months after the surgery, 20% had mild hopelessness, 79% had moderate hopelessness, and 1% had severe hopelessness. These figures 6 months after surgery were 11% hopeless, 31% mildly disappointed, 58% moderately disappointed. The results of the qualitative study resulted in the extraction of three main categories that included enduring the initial suffering, social isolation, and lag of ostomy admission. Conclusion: The relative improvement in suicidal ideation and hopelessness in the present study showed that the mental status of ostomy patients requires more careful attention.